Impact of Informative and Persuasive on Personal Selling: BPL Mobile- A Case Study (International Journal of Innovative Research in Engineering & Management, 2022)
The communication barrier affects the  performance a lot. Especially, the promotion of products  through direct marketing should have maximum and valid  information. The sales team should convey that information,  which will persuade the prospects and leads to purchase the  product. Initially, the sales team fails in sales performance  after all the strategy applied in the market. The solution to the  problem was understood by the sales team. They had aligned  the informative advertisement information and persuasive  advertisement information of BPL mobile ads in personal  selling method. As a result, the strategy had worked and the  team has got the success in sales performance. The personal  communication model really helped the sales team and sales  executive to increase the sales. The case background which is  faced by a sales executive of the BPL mobile is understood  and explained. A suitable case method is referred to construct  the case study. The literatures and sources are studied to find  out the probable problems and most suitable solutions. A case  model (PSCPM) is developed as per the adoption of the  alternative solution by the team. The practical application  assignment is designed for the management students for the  academic purposes. The same model and evaluation of  assignment will be useful for the industry, which possess the  direct marketing activities.
Keywords: Informative advertisement; Persuasive advertisement; Personal Selling; BPL Mobile; PSCPM